2001
DOI: 10.1002/tl.17
|View full text |Cite
|
Sign up to set email alerts
|

Expertise and the Scholarship of Teaching

Abstract: Faculty can move beyond excellence and develop expertise in teaching as well as in the scholarship of teaching. This author explores growth in teaching and in the scholarship of teaching from three different perspectives on the development of expertise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 4 publications
0
27
0
Order By: Relevance
“…Participants in this Delphi study made suggestions for how to respond to some of the issues they identi ed. These issues include the recognition, assessment and evaluation of the scholarship of teaching (Theall & Centra, 2001), the difference between scholarly teaching and the scholarship of teaching (Richlin, 2001), the role of expertise in the scholarship of teaching (Smith, 2001), how to build on and document the wisdom of practice (Weimer, 2001), the role of graduate education and faculty development in educating academics in the scholarship of teaching (Kreber, 2001 b), how to promote the scholarship of teaching within the disciplines (Weston & McAlpine, 2001), and the relationship between research and the scholarship of teaching (Paulsen, 2001). Other scholars have provided excellent discussions of how the scholarship of teaching relates to the other domains of scholarship practised within the disciplines (Healey, 2000;Jenkins, 2000).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Participants in this Delphi study made suggestions for how to respond to some of the issues they identi ed. These issues include the recognition, assessment and evaluation of the scholarship of teaching (Theall & Centra, 2001), the difference between scholarly teaching and the scholarship of teaching (Richlin, 2001), the role of expertise in the scholarship of teaching (Smith, 2001), how to build on and document the wisdom of practice (Weimer, 2001), the role of graduate education and faculty development in educating academics in the scholarship of teaching (Kreber, 2001 b), how to promote the scholarship of teaching within the disciplines (Weston & McAlpine, 2001), and the relationship between research and the scholarship of teaching (Paulsen, 2001). Other scholars have provided excellent discussions of how the scholarship of teaching relates to the other domains of scholarship practised within the disciplines (Healey, 2000;Jenkins, 2000).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…The issue of terminology and definitions still plagues SoTL. Smith (2001a;2001b), Richlin (2001), Richlin and Cox (2004), Hutchings and Shulman (1999), Trigwell and Shale (2005), Nicholls (2004), and many others all confirm the ongoing struggle with coming to a consensus about definitions of terms used in SoTL. Nicholls notes it as a problem in the United Kingdom too, not just in the United States, and "Scholarship of Teaching: Now Too Defined?"…”
Section: ©2006 Journal Of the Scholarship Of Teaching And Learning Fomentioning
confidence: 93%
“…Two of the most common terms defined are "teaching" and "scholarly teaching." Smith (2001a) in "Expertise and the Scholarship of Teaching" defines teaching as all that is involved-both inside and outside the classroom-with helping students learn. In Smith (2001b) differentiates teaching from scholarly teaching by asserting that the latter is informed by educational theory, research, assessment, and methods so that teachers can make appropriate choices to enable their students to be effective learners.…”
Section: General Overviewmentioning
confidence: 99%
“…Individually, faculty members need to review the content of their courses, and as suggested in the literature on pedagogy, we should publicly share aspects of teaching materials and methods (Kreber, 2001;Smith, 2001). As a faculty member in a graduate program in higher education and student affairs, I have substantial control over the content of knowledge I attempt to transmit to my students in a formal class setting.…”
Section: What We Teachmentioning
confidence: 99%